Stability Analysis of Mathematical Models of Corrupt Behavior with Death Penalty Sanction - Prasetya, Adityan Wisnu Yuda; Hidayat, Muhammad Iman (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
Indonesia is one of the countries with a fairly solid economy. Indonesia's foreign exchange reserves reached US$146,383.75 million. This amount should help improve the welfare of its people. However, the fact is that corruption harms the state budget so that people's welfare cannot be fulfilled. As of 2023, Indonesia has lost at least Rp28.412.786.978.089 in 791 cases involving 1,695 suspects. Even after serving their prison sentences, these corruptors' actions fail to provide a significant deterrent effect. Therefore, the imposition of the death penalty is necessary to deter corruption crimes in Indonesia. In this study, we will analyze the stability of the critical point in the mathematical model that incorporates the modified imposition of the death penalty on the corruptor population (C). In the mathematical model of corruption, there are three populations: Susceptible population (S), Corruptor population (C), and Honest population (H). The goal is none other than to minimize and eliminate the corrupt population. The results indicated that there were two critical point conditions: (S1, C1, H1) and (S*, C*, H*). The critical points (S*, C*, H*) show that the corruptor population and honest population still exist. As for the critical point (S1, C1, H1), it appears that the corruptor population and honest population are extinct. This study shows that the imposition of the death penalty in corruption cases can exterminate the corruptor population and certainly has implications for the extinction of the honest population. The value of the benchmark parameter clearly influences this result. Therefore, it can be concluded that applying this research may reduce corruption cases and enhance defense management by promoting accountable state financial management.